ANALISIS PROGRAM DESTINATION BRANDING PROVINSI NUSA TENGGARA BARAT (Studi Deskriptif kualitatif Terhadap Rinjani Traccking Manajement Board pada Taman Nasional Gunung Rinjani) - Lalu Agceiza Rahardipha; Wahyu Hidayat; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
The government launched the destination branding West Nusa Tenggara The first is "VISIT Lombok Sumbawa in 2012" in 2009, which was inaugurated by the President of the Republic of Indonesia Susilo Bambang Yudhoyono. At the time, "VISIT Lombok Sumbawa in 2012" managed to bring in tourists profound, even to achieve an increase of one million tourists in 2012 with the average - average increase of 45% from 2009. The focus in this thesis is a policy - a policy issued by the government and park authority Nansional Mount Rinjani in developing tourism in the region Mount Rinjani National Park with a destination based on the complexity of the appeal, one of the community-based tourism development. Rinjani Treckking Management Board (RTMB) is an institution established by the government, which then cooperates with the National Park of Mount Rinjani in the development of local community-based tourism. In case of problems caused imlementasinya regulations made by the central government, among others, government regulation number 36 of 2010, PERMENHUT No. 4 in 2012, and the PP number 12 of 2014, which affects the clotting RTMB. These problems, berdamak to the development of tourism businesses in the region, because of business competition climate in the area of Mount Rinjani National Park unhealthy, caused is no more supervision by RTMB. Besides Mount Rinjani National Park is famous for the cultural wealth of the communities in the surrounding area. From a variety of cultural attractions owned, among others, menyembe culture, a culture that is unique in mengembala cow, foster a culture of the mountain, all the exploited people, be a tourist attraction to attract tourists. The conclusion of the program destination branding West Nusa Tenggara on Mount Rinjani National Park, namely, the role of RTMB in developing tourism in the National Park of Mount Rinjani is very important, because to make Rinjani as an icon atapun landmark tourism West Nusa Tenggara RTMB approach using 4 complexity Destination Branding that Natural Condition, Politics, Economics, and Society.